A systematic comparison of polar and semipolar Si-doped AlGaN alloys with high AlN content. (22nd October 2020) - Spasevski, Lucia; Kusch, Gunnar; Pampili, Pietro; Zubialevich, Vitaly Z; Dinh, Duc V; Bruckbauer, Jochen; Edwards, Paul R; Parbrook, Peter J; Martin, Robert W
Abstract: With a view to supporting the development of ultra-violet light-emitting diodes and related devices, the compositional, emission and morphology properties of Si-doped n -type Al x Ga1- x N alloys are extensively compared. This study has been designed to determine how the different Al x Ga1- x N crystal orientations (polar (0001) and semipolar (11–22)) affect group-III composition and Si incorporation. Wavelength dispersive x-ray (WDX) spectroscopy was used to determine the AlN mole fraction ( x ≍ 0.57–0.85) and dopant concentration (3 × 10 18 –1 × 10 19 cm −3 ) in various series of Al x Ga1- x N layers grown on (0001) and (11–22) AlN/sapphire templates by metalorganic chemical vapor deposition. The polar samples exhibit hexagonal surface features with Ga-rich boundaries confirmed by WDX mapping. Surface morphology was examined by atomic force microscopy for samples grown with different disilane flow rates and the semipolar samples were shown to have smoother surfaces than their polar counterparts, with an approximate 15% reduction in roughness. Optical characterization using cathodoluminescence (CL) spectroscopy allowed analysis of near-band edge emission in the range 4.0–5.4 eV as well as various deep impurity transition peaks in the range 2.7–4.8 eV. The combination of spatially-resolved characterization techniques, including CL and WDX, has provided detailed information on how the crystal growth direction affects the alloy and dopant concentrations.